2016
DOI: 10.1155/2016/8247014
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Anti-Inflammatory and Analgesic Activities of Ethanol Extract of Stem Bark of SonapathaOroxylum indicum In Vivo

Abstract: Inflammation is all a pervasive phenomenon, which is elicited by the body in response to obnoxious stimuli as a protective measure. However, sustained inflammation leads to several diseases including cancer. Therefore it is necessary to neutralize inflammation. Sonapatha (Oroxylum indicum), a medicinal plant, is traditionally used as a medicine in Ayurveda and other folk systems of medicine. It is commonly used to treat inflammatory diseases including rheumatoid arthritis and asthma. Despite this fact its anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…Natural products are widely used in folk medicine to treat inflammatory conditions, including fever, pain, migraine and arthritis, being targets for the development of new anti-inflammatory drugs. 172 Studies with plant extracts have shown promissory activity. 173 H. isora root extract showed antinociceptive activity in mice.…”
Section: Anti-inflammatory and Analgesic Activitymentioning
confidence: 99%
“…Natural products are widely used in folk medicine to treat inflammatory conditions, including fever, pain, migraine and arthritis, being targets for the development of new anti-inflammatory drugs. 172 Studies with plant extracts have shown promissory activity. 173 H. isora root extract showed antinociceptive activity in mice.…”
Section: Anti-inflammatory and Analgesic Activitymentioning
confidence: 99%
“…A separate experiment was carried out to evaluate the anti-inflammatory activity by xylene-induced ear edema in mice model and the results are listed in Fig. 6 [27]. Although AMD3100 is the only well investigated small molecule CXCR4 antagonist, its bicyclam structure leads to toxicity in the animal model.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in weight of the two ear plugs was taken as a measure of edematous response. The inflammation-suppression percentage was calculated by comparing the drug-treated group to the control group [27]. …”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the in vivo anti-inflammatory activity of the amide-sulfamide compounds, we performed a xylene-induced ear edema experiment [23]. This xylene-induced ear edema model is widely used in the evaluation of inflammatory activity.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in weight of the two ear plugs was taken as a measure of edematous response. The inflammation-suppression percentage was calculated by comparing the drug-treated group to the control group [23]. …”
Section: Methodsmentioning
confidence: 99%